Klausul Akad Pembiayaan Murabahah di Perbankan Syariah - Susi Aryani Manangin (SIGn Jurnal Hukum, 2021)
This study describes the standard clauses in the murabahah financing agreement. This study uses a normative juridical research method. The data was collected using literature study techniques on primary, secondary, and tertiary legal materials. The collected legal material is then analyzed using qualitative data analysis methods, which will conclude the research’s object. The results show that there are 17 standard clauses and a prohibition of inclusion of the exclusion clause in the murabahah financing agreement. Therefore, it is recommended that the Bank and the Customer apply the standard clauses in the murabahah financing agreement. In this case, the Bank and the Customer get guarantees, comfort, and legal protection during the murabahah financing period.